Strategy For MSMe Empowerment of Insana Woven Fabric in the Covid-19 Situation - Emanuel Be (Eduvest - Journal of Universal Studies, 2022)
In the development of the national economy in Indonesia, the priority is Micro, Small and Medium Enterprises (MSMEs). MSMEs are the backbone of the people's economy that can reduce poverty problems and their development is able to expand the economic base and can make a significant contribution to improving the regional economy and national economic resilience. In order for the MSMEs of ikat buna and sotis from Insana to survive the Covid-19 pandemic situation, an appropriate strategy pattern is needed to maintain the existence of MSMEs of Insana's buna and sotis woven fabrics. The research uses qualitative methods with interview data collection methods, participant observation and documentation studies. Then the data analysis technique in this study uses data collection, data reduction, data display and conclusions from data analysis. The results of the study suggest that the pattern of developing MSMEs for insana woven fabrics is by innovating, updating products and then implementing social capital by increasing business networks and increasing income even though the situation is completely limited in the midst of the COVID-19 pandemic.